Land use policy and practice on karst terrains : living on limestone - Fleury, Spencer. (Springer, 2017)
Land use decisions in karst terrains can have immediate and serious impacts on the local landscape and groundwater resources. The existing literature on karst and land use can be difficult to locate in the journals of any of a half-dozen different disciplines. The book Living on Limestone: Land Use Policy and Practice on Karst Terrains brings this interdisciplinary knowledge together in one place, in a format that academics and professionals alike will find accessible, informative and useful. Based on an examination of existing regulations, the experiences and opinions of planners and land use professionals, and quantitative analysis of publicly-available data, Living on Limestone explores how human settlement patterns and urban systems in karst terrains are affected by land use regulations intended to protect karst resources. The book pays particular attention to the questions of whether these regulations will have a noticeable impact on density and on opportunities for economic growth and development in communities that choose to implement them. This analysis serves as the basis for a regulatory framework that may be used to understand the workings of land use regulations in karst terrains, and to aid in the development of such regulations in the future.